Aphakic retinal detachment. Issue 10 (October 1985) - Le Mesurier, R; Vickers, S; Booth-Mason, S; Chignell, A H
Abstract : A study of 132 cases of aphakic retinal detachment (ARD) following mainly intracapsular cataract surgery has been made. Forty-nine cases (37%) were found to have vitreous incarcerated into the cataract section out of a total of 54 (41%) cases who had suffered a vitreous complication during cataract surgery. A study of the characteristics of ARD reveals that those cases having had a vitreous complication in the management of their cataracts are more likely to develop detachment within three months than those not suffering from such a complication. The occurrence of these early post-extraction retinal detachments is not influenced by the presence of underlying axial myopia. When we compared ARD in patients whose cataract extractions had been complicated by vitreous incarceration with those ARDs following uncomplicated cataract surgery, we found that the characteristics of the detachments were very similar. Thus distribution of underlying myopia, extent of detachment, length of time of detachment, and multiplicity and type of retinal holes were generally similar. However, ARD following complicated cataract surgery is more likely to suffer from periretinal fibrosis. The findings confirmed the risk of ARD following complicated intracapsular cataract surgery and support the tendency to perform the extracapsular operation.